Community Perceptions Regarding The Use Of Ville Funds in Development (Case Study in Galala Village, Sirimau District Ambon City) - F.G.Renyut, Selvi; Warbal, Montgomery (Pinisi Business Administration Review, 2023)
The purpose of this study was to describe people's perceptions of the use of village funds in development and to find out the factors that impede the use of village funds in Galala Village, Sirimau District, Ambon City. This study used descriptive research with data collection techniques carried out by interviews, observation and documentation.The results of the research, the planning stages, are less effective, due to the lack of transparency of information conveyed by Galala Village officials to the community and at the implementation stage based on the results of the research it is less effective, where the use of the village fund budget can be resolved properly but due to a lack of transparency of information related to the implementation of activity planning by village government to the community, so that the achievement of the objectives of utilizing village funds carried out in Galala Village is still not effective. whereas at the accountability stage in the process of utilizing village funds in increasing physical development in Galala Village it is less effective, where the preparation of the accountability report does not contain an evaluation of activities that should be carried out with the people of Galala Village.